2021
DOI: 10.1017/aog.2020.88
|View full text |Cite
|
Sign up to set email alerts
|

Development of a clean hot water drill to access Subglacial Lake CECs, West Antarctica

Abstract: Recent drilling successes on Rutford Ice Stream in West Antarctica demonstrate the viability of hot water drilling subglacial access holes to depths >2000 m. Having techniques to access deep subglacial environments reliably paves the way for subglacial lake exploration beneath the thick central West Antarctic Ice Sheet. An ideal candidate lake, overlain by ~2650 m of ice, identified by Centro de Estudios Científicos (CECs), Chile, has led to collaboration with British Antarctic Survey to access Subglacial L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…The access holes created allowed the recovery of sediment samples from the ice stream using samplers on the drill nozzle or from the bed using a simple sediment corer (Makinson, 2021) as well as the in-ice installation of a range of monitoring instrumentation to aid in describing ice-sheet dynamics (Smith, 2020). Disturbance of the basal sediment was also minimised by the ability to manage the borehole water level at breakthrough.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The access holes created allowed the recovery of sediment samples from the ice stream using samplers on the drill nozzle or from the bed using a simple sediment corer (Makinson, 2021) as well as the in-ice installation of a range of monitoring instrumentation to aid in describing ice-sheet dynamics (Smith, 2020). Disturbance of the basal sediment was also minimised by the ability to manage the borehole water level at breakthrough.…”
Section: Discussionmentioning
confidence: 99%
“…Sediment sampling was attempted in the borehole (Fig. 23F) using a new hammer arrangement (Makinson, 2021). While the new mechanism operated successfully, no indication of penetration was noted during the hammering process and, following recovery, damage to the corers' cutter head suggested that a boulder of some description was the probable cause of the obstruction (Smith, 2020).…”
Section: Drilling Field Season 2018/19mentioning
confidence: 99%
See 1 more Smart Citation
“…The next field testing opportunity for the BMS will be during the planned test season for the Subglacial Lake CECs (Centro Estudios Cientificos) Clean Hot Water Drill project (see Makinson and others, 2021). This project will primarily require the hole diameter measurements, however the full functionality would be beneficial.…”
Section: Future Improvementsmentioning
confidence: 99%
“…The key attributes of this new mechanical percussion hammer mechanism are its unrestricted operational depth range, relatively simple operation, reduced learning curve and easy field maintenance, which extends the usefulness of the BAS-UWITEC coring system particularly in remote field environments where it is prohibitive to use larger drilling infrastructure. In preparation for the planned clean accessing of Subglacial Lake CECs in West Antarctica (Makinson and others, 2021) and sampling of its sediments almost 3000 m below the ice-sheet surface, further modifications to the corer hammer section and tether are required. The modifications are necessary to conform to stringent cleanliness standards in preventing chemical or biological contamination of the subglacial lake environment.…”
Section: Summary and Future Upgradesmentioning
confidence: 99%